Communicative techniques as facilitator elements for learning listening comprehension skills focus on puppet among first graders at Loma Colorada Elementary School - Ríos Iglesia, Johana Lorena; Rivera Villarreal, Wendy Elena (David, Panamá : UDELAS, 2014)
This research project is focused on meaningful communicative techniques with puppets in order to provide a favorabke learning alternative to determinte the extent of listening comprehension in a second languaje in first graders. The authors have worked through all the strategies or procedure which purpose is to provide students in first grade with practical options to stimulate progress in the acquisition and development of comprehension (input) and communication abilities (output) in the English Language.
TABLE OF CONTENT TABLE INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I: ANTECEDENTS AND STATEMENT OF THE PROBLEM 1.1. Antecedents 1.1.1. Definition and characteristic puppets 1.1.2. History of puppets 1.1.3. Contribution of puppets in education 1.2. Statement of the problem 1.3. Objectives 1.3.1. General objective 1.3.2. Specific objectives 1.4. Justification 1.5. Scope and delimitation 1.5.1. Scope 1.5.2. Delimitation CHAPTER II: THEORETICAL FRAMEWORK 2.1. Communicative techniques 2.1.1. Communicative techniques with puppets 2.1.2. Puppets 2.1.3. Benefits of using puppets 2.1.4. Comprehension skills 2.2. Characteristic of communicative techniques 2.2.1. Dynamism of communication 2.2.2. Listening skills 2.2.3. Self confidence 2.2.4. Social interaction among students 2.3. The english teacher's role using communicative techniques with puppets 2.3.1. Facilitator of procedures and resources to achieve objectives 2.3.2. Content specialist 2.3.3. Teacher as affetive leaders 2.3.4. Competency - based learning 2.4. Communicative techniques 2.4.1.Dramatization 2.4.2. Storytelling 2.4.3. Singing songs along 2.4.4. Tongue- twister 2.4.5. Riddles 2.4.6. Dialogues 2.5. Motivation in communicative techniques 2.5.1. Types of motivation 2.5.2. Motivational impact of values adn belief system of human beings 2.5.3. Maslow's hierarchy of motivation CHAPTER III: METHODOLOGICAL ASPECT 3.1. Type of research 3.1.1. Qualitative research 3.1.2. Exploratory research 3.2. Information sources 3.2.1. Material sources 3.2.2. Human sources 3.3. Variable system 3.3.1 Modern communicative techniques as facilitation elements for learning listening comprehension skils employing puppets in school first graders 3.3.1.2. Conceptual definition 3.3.1.3. Instrumental definition 3.3.1.4. Operational definition 3.3.2. The most common features of communicative techniques as facilitation elements for learning listening comprehension skills focusing on puppetry in first graders 3.3.2.1. Conceptual definition 3.3.2.2. Instrumental definition 3.3.2.3. Operational definition 3.3.3. The teacher's role while using communicative techniques with puppets 3.3.3.1. Conceptual definition 3.3.3.2. Instrumental definition 3.3.3.3. Operational definition 3.3.4. Communicative techniques that can e used to develop listening comprehension skills with puppets 3.3.4.1. Conceptual definition 3.3.4.2. Instrumental definition 3.3.4.3. Operational definition 3.3.5. Motivation as part of communicative techniques that help the students to develop listening comprehension skills focus on puppets 3.3.5.1. Conceptual definition 3.3.5.2. Instrumental definition 3.3.5.3. Operational definition CHAPTER IV<. ANALYSIS AND RESULTS 4.1. Analysis of the survey applied to teacher at Loma Colorada Elementary School 4.1.1. Variable 2: The characteristic of communicative techniques as active learning elements for listening comprehension skills focus on puppets 4.1.2. Variable 3: Th english teacher's role in the implementation communication technique with puppets 4.2. Analysis of the survey applied to parent at Loma Colorada Elementary School 4.2.1. Variable 2: The characteristic of communicative techniques as facilitator elements for learning listening comprehension skills focus on puppets 4.2.2. Variable 5: The role of motivation in communicative techniques that help the sudents to develop listening comprehension skills focus on puppets 4.3. Analysis of the survey applied to students at Loma Colorada Elementary School 4.3.1. Variable 4: Communicative techniques can be used to develop listening comprehension skills using puppets Conclusion Recomendation Bibliographical references Annexes
Incluye Table of content
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés.
Incluye Bibliografía
No se presta a domicilio.
No se saca fotocopias.
Keywords: ENGLISH -- TESIS; INGLÉS -- TESIS; LICENCIATURA EN DOCENCIA EN INGLÉS - TESIS; LOMA COLORADA ELEMENTARY SCHOOL; COMPRENHENSION SKILLS